1973
DOI: 10.1136/pgmj.49.567.18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of propranolol and Ro 3-3528 in hyperthyroid tachycardia and dysrhythmias

Abstract: SummaryRo 3-3528, a non-selective 3-adrenoceptor blocking drug which lacks intrinsic activity, produces a doseresponse effect in hyperthyroid tachycardia, and shows no dysrhythmic properties. In hyperthyroid patients,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1974
1974
1974
1974

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the present study, practolol did have a dose-dependent effect on exercise heart rate in hyperthyroid patients. (Turner & Hill, 1968;Turner, 1970;Arbab & Turner, 1971;Phillips et al, 1973). These present observations would suggest that reduction in resting heart rate is not representative of the ,3-blocking activity of these drugs and that, whilst propranolol is obviously more effective than practolol in hyperthyroid patients, this merely reflects the comparable activity of these two drugs in normal subjects, and cannot be held to support the idea that patients with hyperthyroidism are unduly sensitive to the effects of catecholamines.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In the present study, practolol did have a dose-dependent effect on exercise heart rate in hyperthyroid patients. (Turner & Hill, 1968;Turner, 1970;Arbab & Turner, 1971;Phillips et al, 1973). These present observations would suggest that reduction in resting heart rate is not representative of the ,3-blocking activity of these drugs and that, whilst propranolol is obviously more effective than practolol in hyperthyroid patients, this merely reflects the comparable activity of these two drugs in normal subjects, and cannot be held to support the idea that patients with hyperthyroidism are unduly sensitive to the effects of catecholamines.…”
Section: Discussionmentioning
confidence: 65%
“…This test could be performed easily and, if necessary, frequently, and would avoid the difficulties of carrying out strenuous exercise in the presence of either thyrotoxic myopathy or cardiovascular disease. Further support for the use of such a test to evaluate ,B-adrenoceptor blocking agents in Practolol, and other f-adrenoceptor blocking drugs with intrinsic sympathomimetic activity, have been labelled as inferior to propranolol and other drugs without intrinsic activity in the treatment of hyperthyroidism but only on the basis of their effect on resting heart rate (Turner & Hill, 1968;Turner, 1970;Arbab & Turner, 1971;Phillips et al, 1973). These present observations would suggest that reduction in resting heart rate is not representative of the ,3-blocking activity of these drugs and that, whilst propranolol is obviously more effective than practolol in hyperthyroid patients, this merely reflects the comparable activity of these two drugs in normal subjects, and cannot be held to support the idea that patients with hyperthyroidism are unduly sensitive to the effects of catecholamines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hill & Turner (1968) studied the effects of Ro 3-3528 on the heart rate during rest, after administration of isoprenaline and during exercise. Phillips, Turner, Houghton & Ferriman (1973) found that this drug was similar to propranolol in controlling hyperthyroid tachycardia. In animal studies, Ro 34787 differed from the earlier drug in possessing greater potency, a longer duration of action and some degree of intrinsic sympathomimetic activity, being approximately one-quarter as active in this respect as practolol (Parkes & Parks, 1971, personal …”
Section: Introduction Methodsmentioning
confidence: 98%